ChemInform Abstract: Synthetic Routes Toward Asymmetrically Substituted (Functionalized) 4H‐Cyclopenta[2, 1‐b:3, 4‐b′]dithiophenes. Issue 15 (15th April 2014) - Vanormelingen, Wouter; Verstappen, Pieter; Maes, Veronique; Bevk, David; Lutsen, Laurence; Vanderzande, Dirk; Maes, Wouter
Abstract A convenient two‐step sequence is presented for the conversion of ketone (I) into asymmetrically dialkylated derivatives via Wittig‐type olefination followed by regioselective alkylation of the exocyclic double bond.